Rural development strategy and perspective - Bhadouria, B. P. S.; Dua, S. C. (Delhi, India : Anmol Publications : Distributed by Anupama Publishers and Distributors, 1986)
Study; with reference to Uttar Pradesh, India.
Spine title: Rural development strategy & perspective.
Includes bibliographical references and indexes.
Amirul
Keywords: Rural development -- India -- Uttar Pradesh; Regional planning -- India -- Uttar Pradesh